Optimization of central composite design of ferric reducing antioxidant power from cocoa (Theobroma cacao) shell using Ultrasound-assisted Technique - Md Yusof, A. H; Abd Gani S. S, S. S; Zaidan, U. H; Halmi, M. I. E.; Abdul Wahab, N (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Cocoa (Theobroma cacao) shell is waste product discarded from the cocoa industry. About 75% of cocoa fruit is waste. Inthe present study, antioxidant assay (ferric reducing antioxidant power) for cocoa shell was optimized by response surface methodology with three factors and five levels of the model. The factorswere set at solvent percentages (70-90%), temperatures (45-65°C), and ultrasound irradiation times (30-60 minutes at a constant frequency of 40 kHz. Optimum conditions were established at 70%, 65°C,and 30 minutes respectively, at a concentration of 1.41±0.01 µmoles/L. The analysis of variance (ANOVA)revealed that the coefficient of determination (R2 ) was 0.9650 at an optimum concentration of1.41±0.01 µmoles/L. Under these conditions, the predicted value was established at1.37, slightly lower than the experimental value. However, the data fit the model with significance at p<0.0001 and lack of fit test at p = 0.5091. The study confirmed that the model equation could be used to predict future observation within the model design range.